2022
DOI: 10.1002/dad2.12284
|View full text |Cite
|
Sign up to set email alerts
|

The neuroinflammatory marker sTNFR2 relates to worse cognition and tau in women across the Alzheimer's disease spectrum

Abstract: Introduction Despite women showing greater Alzheimer's disease (AD) prevalence, tau burden, and immune/neuroinflammatory response, whether neuroinflammation impacts cognition differently in women versus men and the biological basis of this impact remain unknown. We examined sex differences in how cerebrospinal fluid (CSF) neuroinflammation relates to cognition across the aging–mild cognitive impairment (MCI)–AD continuum and the mediating role of phosphorylated tau (p‐tau) versus other AD biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Female APOE ε4 allele carriers with high levels of CSF IL‐12p40, TNF‐α, and IL‐9 had the greatest risk of progression, 183 and higher levels of CSF sTNFR2 were associated with worse cognition, mediated by CSF p‐tau181, in women but not men. 185 Higher levels of eight proinflammatory CSF biomarkers combined with lower levels of cerebrovascular disease, measured by pulse pressure, were associated with higher levels of CSF Aβ42 in CU ADNI participants. 186 However, in MCI participants this combination was associated with higher levels of CSF p‐tau181 and t‐tau but not Aβ42.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 90%
See 1 more Smart Citation
“…Female APOE ε4 allele carriers with high levels of CSF IL‐12p40, TNF‐α, and IL‐9 had the greatest risk of progression, 183 and higher levels of CSF sTNFR2 were associated with worse cognition, mediated by CSF p‐tau181, in women but not men. 185 Higher levels of eight proinflammatory CSF biomarkers combined with lower levels of cerebrovascular disease, measured by pulse pressure, were associated with higher levels of CSF Aβ42 in CU ADNI participants. 186 However, in MCI participants this combination was associated with higher levels of CSF p‐tau181 and t‐tau but not Aβ42.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 90%
“…The detrimental effects of neuroinflammation appear to be exacerbated by various other factors such as sex, APOE status, and cerebrovascular disease. Female APOE ε4 allele carriers with high levels of CSF IL‐12p40, TNF‐α, and IL‐9 had the greatest risk of progression, 183 and higher levels of CSF sTNFR2 were associated with worse cognition, mediated by CSF p‐tau181, in women but not men 185 . Higher levels of eight proinflammatory CSF biomarkers combined with lower levels of cerebrovascular disease, measured by pulse pressure, were associated with higher levels of CSF Aβ42 in CU ADNI participants 186 .…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 98%
“…The Shapiro-Wilk test and corresponding histograms were used to identify primary outcome variables with non-normal distributions. All three (Aβ Centiloid value, EF score, and EM score) met this criteria (Table S1, Figures S1-S3) and, due to the inclusion of negative values, were cube-root transformed to correct for this (33)(34)(35). Prior to transformation, outliers were detected using the 'qqplot' function in R (36) with one outlier being identified for Aβ Centiloid score and removed from analyses (Figure S4).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Sex differences in neuroinflammatory response may be particularly relevant among older adults, given that menopause potentiates low-grade, chronic inflammation. A post-mortem study showed that microglial activation in AD pathogenesis was disproportionately higher in females than in males [ 33 ], while data from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) showed that soluble tumor necrosis factor receptor 2 (sTNFR2) cerebrospinal fluid (CSF) concentrations were related to poorer cognition in women only [ 34 ].…”
Section: Genes Neuroinflammation and Dementiamentioning
confidence: 99%